Perspectives from the private sector on the trade facilitation tools and instruments being implemented in SADC and COMESA : a case of Malawi - Biliwita, Chifundo (GSB: Faculty, 2016)
The researcher observed that little or no attention was being paid to the realities and experiences that the Malawian private sector faced when using various Trade Facilitation (TF) measures being implemented by Malawi within the context of Southern African Development Community (SADC) and Common Market for Eastern and Southern Africa (COMESA) and when trading within the SADC and COMESA regions. Notable gaps were identified in the overall TF management process in Malawi. This study made an assessment of each TF measure that Malawi introduced and implemented within the context of SADC and COMESA, analysing its benefits and challenges from a private-sector perspective. Questionnaires and interviews were used to get in-depth, objective and honest perspective from the private sector on these TF measures. The findings of the study revealed that the various TF measures implemented brought: universal and common tariff coding and measurement units for goods; certainty and predictability in the classification of goods; speedy release of goods; reduced delays in transit time; preferential rates of duty for the private sector. Other anticipated results include a further reduction in insurance and bond costs and faster sharing of information, once other measures are fully implemented. In brief, most TF measures reduced the cost of doing business. However, challenges were also found and they included: limited and selective awareness and involvement of the private sector during both consultation and implementation of the TF instruments; unharmonised implementation of the TF measures; notable lack of trust between customs and trade community; notable delays in implementation of some measures; no post-mortem and audit of the TF measures to check and confirm the successes and challenges that the TF measures have brought into the trade chain; poor selection and management of stakeholders to involve; secretive acts over TF information; and weaknesses in the legal frameworks of SADC and COMESA. A further analysis of these issues is presented in chapter four and chapter five.